Miswak versus Toothpaste: Analysis of Function and Relevance in Dental Health Maintenance According to Hadith and Modern Health Perspective - Hutauruk, Mathias Raihan Narayan; Remanggi, Salasi; Qorib, Fathul (Al-Jadwa: Jurnal Studi Islam, 2025)
Miswak and toothpaste represent two separate methods for preserving oral hygiene; miswak is favored in Islam, whereas toothpaste is favored in the modern period. While both offer advantages, there is limited research that compares their medical effects and alignment with the Sunnah. This study aims to examine their function and relevance in promoting oral health. The main objective of this study is to answer the question of whether the function of miswak has been replaced by toothpaste or if miswak still has a unique role that is important for dental health and the spiritual identity of Muslims. The methods used include analysis of hadith texts and a review of scientific literature related to the benefits of miswak and toothpaste from a health perspective. The results of the study indicate that miswak contains active substances such as natural fluoride, antibacterials, and antioxidants that are beneficial for dental and gum health, which are also found in modern toothpaste. Although toothpaste offers practicality, miswak still has irreplaceable value, both in terms of health and spirituality. The combination of the two is recommended as an integrative approach in maintaining dental health according to Islamic teachings and modern health needs.